Soft Component of Emission from Channeled Electrons in a Silicon Crystal; Russian Physics Journal; Vol. 44, iss. 3 - Vnukov I. E.; Kalinin B. N.; Kiryakov A. A.; Naumenko G. A. Gennadiy Andreevich; Padalko D. V.; Potylitsyn A. P. Alexander Petrovich (2001, 2001)
Title screen